Motion pictures as underestimated sources of migration studies: the case of Ö. Lütfi Akad’s gelin, düğün and diyet trilogy - Bilgen Aydın, Sevim; Sevim, Seçkin (My University, 2018)
Platonic rigid separation between the arts and sciences reached its climax with the emergence of positivism. Centuries long dualistic understanding of reality, whereby there is either the reason or sense experience, created an artificial wall between the arts and sciences. With the emergence of the global village and post-modernity, rigid separation between the arts and sciences began to disappear. In today’s ‘fragile society’ ‘liquid society’ ‘virtual society’ and ‘risk society’ the holistic approach to the reality has become inevitable feature of the post-modern societies. In today’s world, both the arts and sciences are inevitable for the holistic study of any phenomenon, including the phenomenon of motion pictures and migration. Today the artists have become brave explorers who dared to enter the fields that were not touched by the scientists yet. Using holistic approach this study aims to explore the artistic and motion pictures dimensions of migration by considering experiential knowledge and story experiences. This paper aims to show how the cinema is the most efficient art form that can turn an experiential knowledge into a story. The trilogy named Gelin (1973), Düğün (1974), Diyet (1975) of Ö. Lütfi Akad (1916-2011), one of the founder directors of Turkish Cinema, is about internal migration in Turkey. Content analysis of Lütfi Akad’s trilogy clearly show what being a migrant meant in the big cities of Turkey during the 1960’s and 1970’s. In today’s Turkey, the society can identify with the characters of this trilogy as to understand present- day predicament, challenges and prospects of migrant societies. This paper will certainly demonstrate strong relationship between the motion picture and migration.
Keywords: Motion Pictures, Post-modernity, Migration, Lütfi. Akad’s Trilogy